A Human Resource Development Strategies in Enhancing the Welfare of As-Sunnah Deli Serdang Islamic Higher Education Institution in North Sumatra - Andri Rivai; Sahmiar Pulungan; Maryam Batubara (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study analyzes human resource management development strategies to improve the welfare of Human Resources (SDI) in STAI As-Sunnah. The results of this study show strategies that can be applied, including curriculum development, teacher quality improvement, strategic partnerships, infrastructure improvements, and academic mentoring programs. The results of this study provide recommendations to improve the welfare of SDI in STAI As-Sunnah and provide direction for decision-makers and related parties in the development of more effective and sustainable human resource management. In this study, conclusions will also be drawn based on the results of the study, including human resource management development strategies, utilization of internal strengths and external opportunities, overcoming internal weaknesses, and handling external threats. The purpose of this study is to provide recommendations that can help STAI As-Sunnah in improving the welfare of SDI so that they can get quality education and support the development of their potential optimally.